Positive electrode material, preparation method thereof and lithium ion battery

By mixing single crystal and polycrystalline materials in proportion, the gas production problem of high-nickel positive electrode materials is solved, high compaction and long circulation performance are achieved, and the safety performance and storage capacity of the battery are improved.

CN119725420APending Publication Date: 2025-03-28SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311279957.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

High-nickel positive electrode materials are prone to production gas problems during use, resulting in battery failure and safety risks, and the existing technology is difficult to effectively solve this problem.

Method used

By mixing single crystal material and polycrystalline materials in a certain proportion, small single crystal particles can evenly adhere to the large polycrystalline particles and fill their voids, improving the bulk density and electrochemical properties of the material and reducing gas production risks.

Benefits of technology

The high compaction and long circulation performance of the positive electrode material are achieved, the gas production is reduced, and the safety performance and storage capacity of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725420A_ABST
    Figure CN119725420A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a preparation method thereof and a lithium ion battery, and relates to the technical field of lithium ion batteries. The positive electrode material comprises a single crystal material and a polycrystalline material, the single crystal material is composed of primary particles, and the polycrystalline material is composed of secondary spherical particles formed by gathering the primary particles; the average particle size D of the positive electrode material satisfies D = D1 * K + D2 * L, where 3 [mu] m < D1 < 9 [mu] m, 10 [mu] m < D2 < 20 [mu] m, 0 < = K < = 1, 0 < = L < = 1, and K + L = 1. The preparation method of the positive electrode material comprises the following steps: respectively preparing a polycrystalline positive electrode material and a single-crystal positive electrode material from raw materials including a positive electrode precursor, a lithium source, a doping agent and a coating agent; and mixing in proportion to obtain the positive electrode material. The polycrystalline material and the single crystal material are mixed, the capacity of the polycrystalline material is exerted, meanwhile, the high compressive strength of the single crystal material is considered, gas production of the positive electrode material is inhibited, and the safety performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] As the reserves of petrochemical energy, mainly oil, coal and natural gas, continue to decrease, and as carbon dioxide produced by petrochemical energy causes global warming as a greenhouse gas, people have paid extensive attention to and thought about the power source of future social development. As a new type of high-energy green battery, lithium-ion power battery has become a research hotspot in new energy. The positive electrode material in the battery is the most critical component of the battery, and its performance directly determines the performance level of the entire battery. At present, common positive electrode materials include lithium iron phosphate, ternary, lithium manganese oxide, and lithium-rich. Although lithium iron phosphate has outstanding cycle life and safety, its capacity density and low temperature performance seriously affect its application range; lithium manganese oxide is very cheap, but its energy density is also low; lithium-rich materials have high capacity and high voltage, but their current service life is seriously insufficient; and ternary (NCM) materials have good comprehensive performance and are currently the most important positive electrode materials in the field of power batteries.

[0003] Although lithium-ion batteries have been widely used in zero-emission electric vehicles, their energy density is not high enough and their single-charge range is short, which cannot meet the needs of the majority of automobile consumers. Therefore, there is an urgent need to further improve the energy density of lithium-ion power batteries. The development of positive electrode materials with higher specific energy is the key to improving the energy density of lithium-ion batteries. Nickel-rich positive electrode materials have higher discharge capacity (200-230mAh / g) and higher energy density (>800Wh / kg), and their production cost is much lower than LiCoO2, making them the focus of current research. As the nickel content in high-nickel materials increases, their structural stability and the interface of the material become more unstable, especially the gas production problem of the positive electrode material, which can easily lead to battery failure and short circuit, and then cause fire and explosion, affecting the safety behavior of the battery. There are two main reasons for gas production: the first is that the material is very likely to undergo a phase change process from layered structure to spinel structure to inactive rock (H2 phase to H3 phase transition) during the charge and discharge process, which causes the battery capacity and cycle performance to decay. This process will cause the lattice in the material to lose oxygen. When deep lithium is removed during the charge and discharge process, the charge compensation on the surface of the material is caused by the loss of electrons by oxygen, thereby releasing oxygen. The oxygen released by the material lattice reacts with the electrolyte to produce gases such as carbon dioxide and hydrogen, which cause the battery to bulge and deform, leading to safety problems. The second is that during the rolling process of the positive electrode material, the polycrystalline particles are broken due to insufficient strength and overpressure. The broken particles increase the contact area with the electrolyte during the charge and discharge cycle, resulting in intensified side reactions and particle pulverization. It also produces a large amount of gas, which causes the battery to fail. Conventional technical solutions use a mix of large polycrystalline particles and small polycrystalline particles to improve compaction and avoid gas production caused by micropowder problems in the material. However, due to the small particle size and poor particle strength of small polycrystalline particles, small particles are prone to breakage under high compaction. Small particles may also agglomerate and cannot be effectively and evenly dispersed among large particles. In addition, their pulverization is aggravated after contact with the electrolyte. Although the initial gas production problem is suppressed to a certain extent, after a certain number of cycles, the gas production problem will gradually worsen, resulting in battery failure. Although high-nickel single crystals can significantly suppress the gas production problem, their surface activity and oil absorption value are high during use, leading to agglomeration problems and difficulty in exerting capacity performance.

[0004] Therefore, the gas production of high-nickel positive electrode materials is a major problem that the power and energy lithium-ion battery industries urgently need to solve. The solution to this problem will also determine whether high-energy-density power batteries can be widely used in other fields such as electric vehicles in the future. Summary of the invention

[0005] The purpose of the present application is to provide a positive electrode material and a preparation method thereof and a lithium ion battery.

[0006] To achieve the above objectives, the technical solution of this application is as follows:

[0007] In a first aspect, the present application provides a positive electrode material, including a single crystal material and a polycrystalline material, wherein the single crystal material is composed of primary particles, and the polycrystalline material is composed of secondary spherical particles formed by aggregation of primary particles;

[0008] The average particle size D of the positive electrode material satisfies D=D1*K+D2*L, wherein D1 is the average particle size of the single crystal material, D2 is the average particle size of the polycrystalline material, K is the mass percentage of the single crystal material, L is the mass percentage of the polycrystalline material, 3μm<D1<9μm, 10μm<D2<20μm, 0≤K≤1, 0≤L≤1, and K+L=1.

[0009] More preferably, 0.6≤K≤1, 0≤L≤0.4.

[0010] In a second aspect, the present application provides a positive electrode material, including a single crystal material and a polycrystalline material, wherein the single crystal material is composed of primary particles, and the polycrystalline material is composed of secondary spherical particles formed by aggregation of primary particles;

[0011] The positive electrode material satisfies 0.5<N1 / (N1+N2)<1, wherein N1 is the number of primary particles in the cross-section of the secondary spherical particles in the cross-section of the positive electrode material particles, N2 is the number of primary particles in the cross-section of the positive electrode material particles, and the cross-section of the positive electrode material particles contains at least one complete secondary spherical particle.

[0012] More preferably, the positive electrode material satisfies 0.8<N1 / (N1+N2)<1.

[0013] In combination with the first aspect and / or the second aspect, in one embodiment of the present application, the positive electrode material satisfies at least one of the following conditions:

[0014] A. The general chemical formula of the positive electrode material is: Li a Ni x Co y N z M 1-x-y-z O2, wherein 0.990≤a<1.1, 0.60≤x<1, 0<y<0.3, 0<z<0.3, N is Mn or Al, and M is at least one of Al, Ti, Zr, Mg, Sr, W, Ca, Ba, Nb, W, B, and Y;

[0015] B. The surface of the single crystal material and the surface of the polycrystalline material both contain a coating layer;

[0016] C. The BET specific surface area of ​​the positive electrode material is 0.1 m 2 / g-1.0m 2 / g;

[0017] D. The oil absorption of the positive electrode material V≤30ml / 100g;

[0018] E. The BET specific surface area of ​​the positive electrode material and the oil absorption V of the positive electrode material satisfy: 25.0≤V / BET≤35.0.

[0019] In a third aspect, the present application further provides a method for preparing the positive electrode material according to the first aspect and / or the second aspect, comprising:

[0020] Using raw materials including a positive electrode precursor, a lithium source, a dopant and a coating agent, polycrystalline positive electrode materials and single crystal positive electrode materials are prepared respectively;

[0021] The polycrystalline positive electrode material and the single crystal positive electrode material are mixed in proportion to obtain the positive electrode material.

[0022] In conjunction with the third aspect, in one embodiment of the present application, the preparation method satisfies at least one of the following conditions:

[0023] (1) The preparation method of the polycrystalline positive electrode material comprises: mixing the positive electrode precursor, the lithium source and the dopant, and performing a first sintering to obtain a polycrystalline matrix material; mixing the polycrystalline matrix material with the coating agent, placing the polycrystalline matrix material in a single cone for heat treatment and coating, and obtaining a polycrystalline matrix containing a primary coating; mixing the polycrystalline matrix containing the primary coating with the coating agent, and performing a second sintering to obtain the polycrystalline positive electrode material;

[0024] (2) The method for preparing the single crystal positive electrode material comprises: mixing the positive electrode precursor, the lithium source and the dopant, and performing a third sintering to obtain a single crystal matrix material; mixing the single crystal matrix material with the coating agent, and performing a fourth sintering to obtain a single crystal matrix containing a primary coating; mixing the single crystal matrix containing a primary coating with the coating agent, and performing a fifth sintering to obtain the single crystal positive electrode material.

[0025] Further preferably, the method for preparing the polycrystalline positive electrode material satisfies at least one of the following conditions:

[0026] (3) The molar ratio of the metal element in the positive electrode precursor to the lithium element in the lithium source is 1: (0.99-1.1);

[0027] (4) The first sintering and the second sintering are both carried out in an oxygen atmosphere;

[0028] (5) The gas pressure of the first sintering and the second sintering is 5Pa-20Pa;

[0029] (6) The first sintering heating rate is 1 ° C / min-5 ° C / min, the temperature is raised to 600 ° C -800 ° C, and the temperature is kept for 5h-10h;

[0030] (7) When the heat treatment coating is performed, the single cone is in a vacuum state;

[0031] (8) The heat treatment coating temperature is 150 ℃ -300 ℃, the time is 5h-15h;

[0032] (9) The heating rate of the second sintering is 1℃ / min-5℃ / min, the temperature is raised to 250℃-550℃, and the temperature is kept for 4h-10h.

[0033] Further preferably, the method for preparing the single crystal positive electrode material satisfies at least one of the following conditions:

[0034] (10) The molar ratio of the metal element in the positive electrode precursor to the lithium element in the lithium source is 1: (0.99-1.1);

[0035] (11) The third sintering, the fourth sintering and the fifth sintering are all carried out in an oxygen atmosphere;

[0036] (12) The gas pressure of the third sintering, the fourth sintering and the fifth sintering is 5Pa-20Pa;

[0037] (13) The heating rate of the third sintering is 1°C / min-5°C / min, the temperature is raised to 700°C-950°C, and the temperature is kept for 5h-10h;

[0038] (14) The heating rate of the fourth sintering is 1 ° C / min-5 ° C / min, the temperature is raised to 550 ° C -700 ° C, and the temperature is kept for 5h-10h;

[0039] (15) The heating rate of the fifth sintering is 1°C / min-5°C / min, the temperature is raised to 250°C-500°C, and the temperature is kept for 4h-10h.

[0040] In conjunction with the third aspect, in one embodiment of the present application, the preparation method further satisfies at least one of the following conditions:

[0041] (16) The chemical formula of the positive electrode precursor is Ni b Co c N 1-b-c (OH)2, wherein 0.60≤b<1, 0<c<0.3, and N is Mn or Al;

[0042] (17) The lithium source comprises at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium oxalate, lithium sulfate, lithium chloride and lithium nitrate;

[0043] (18) The dopant is selected from an oxide or hydroxide containing at least one element of Al, Ti, Zr, Mg, Sr, W, Ca, Ba, Nb, B, and Y;

[0044] (19) The coating agent includes a metal oxide, a metal hydroxide, a phosphate, a sulfate, a solid electrolyte material or a conductive polymer;

[0045] (20) The mass ratio of the polycrystalline positive electrode material to the single crystal positive electrode material is (10-90): (90-10);

[0046] (21) The mixing of the polycrystalline positive electrode material and the single crystal positive electrode material is carried out under the protection of nitrogen gas.

[0047] In a fourth aspect, the present application further provides a lithium-ion battery, comprising the positive electrode material described in the first aspect and / or the second aspect.

[0048] Beneficial effects of this application:

[0049] The positive electrode material of the present application mixes single crystal material and polycrystalline material together, so that small single crystal particles can adhere to the periphery of large polycrystalline particles and fill the gaps between large polycrystalline particles, thereby improving the problem of easy agglomeration of single crystal particles themselves, making the mixed positive electrode material more densely stacked, increasing the stacking density, and improving the electrochemical performance of the positive electrode material.

[0050] The positive electrode material of the present application is a mixture of single crystal material and polycrystalline material. By calculating the number of primary particles of polycrystalline material and the number of primary particles of single crystal in the particle cross section, it can be further verified that the single crystal particles are uniformly dispersed around the polycrystalline secondary spherical particles and can fill the gaps between the polycrystalline secondary spherical particles, thereby improving the compaction of the positive electrode material, reducing gas production, and improving the cycle performance.

[0051] The preparation method of the positive electrode material of the present application has a simple process, strong operability, and can be mass-produced. Specifically, the present application uses a dopant and a coating agent as raw materials to modify the surface of a single crystal material and a polycrystalline material, respectively, thereby reducing the oil absorption value of the positive electrode material. Among them, single crystal materials are in an energy unstable state due to their small particle size, large surface atomic ratio, large specific surface area, and large surface energy. They are easy to agglomerate to form secondary particles and have side reactions with the electrolyte. Therefore, surface modification of single crystal materials can reduce the reactive interface between single crystal materials and electrolytes, reduce agglomeration between particles, reduce the surface energy of particles, reduce side reactions, inhibit the dissolution of metal ions, and optimize the cycle performance of materials. The particle strength of polycrystalline materials is relatively smaller than that of single crystals, and the stacking gaps between particles are larger. In addition, their friction and collision will destroy the surface morphology structure of the particles. There are many grain boundaries between particles and the specific surface area is relatively small. Therefore, the surface energy of large polycrystalline particles is improved by surface modification and coating. At the same time, the surface of large polycrystalline particles is modified and protected to reduce surface structure damage caused by friction and collision, stabilize the oxygen atoms on the surface of the material, inhibit surface structure changes during charging and discharging, and improve its cycle and storage performance.

[0052] The above-mentioned positive electrode material is used in the lithium-ion battery provided in the present application, which reduces the gas production of the positive electrode material and improves the safety performance of the battery. At the same time, by mixing single crystals and polycrystalline materials, the positive electrode material has the characteristics of high compaction, thereby improving the storage performance and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0054] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1;

[0055] Figure 2 The SEM image of the cross section of the positive electrode material prepared in Example 1 after cutting;

[0056] Figure 3 The gas production of the positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-2 in the battery;

[0057] Figure 4 This is the particle size distribution diagram of the positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0058] As used herein:

[0059] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus. The conjunction "consisting of" excludes any unspecified element, step, or component.

[0060] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0061] In these examples, parts and percentages are by mass unless otherwise indicated.

[0062] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0063] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0064] A large number of researchers have studied the problem that high-nickel positive electrode materials are prone to gas production, which in turn affects the safety performance of batteries. Among them, in some studies, the volume energy density of the positive electrode material is improved by treating the polycrystalline large-particle positive electrode material and the polycrystalline small-particle positive electrode material with different added elements, and then mixing them in a certain proportion, thereby improving the cycle performance and charging rate. However, because the small particles are polycrystalline, they have low strength and are easy to break during the pole piece rolling process, and there is still a risk of gas production. There may also be agglomeration of small particles, which cannot be effectively and evenly dispersed between large particles, and the particle size distribution is imbalanced, deviating from the expected effect, thereby affecting the electrochemical performance of the battery. Furthermore, in some later studies, by carbon coating the surface of polycrystalline small particles and then mixing them with polycrystalline large particles, the damage during the pole piece rolling process can be improved, but due to the strength of the polycrystalline small particles themselves, although there is a certain improvement compared to before, the effect is not ideal.

[0065] Based on this, the inventors of the present application conceived of providing a positive electrode material that is a mixture of single-crystal primary particles and polycrystalline secondary spherical particles. This can overcome the problems of cycle and storage performance deviations caused by the instability of the particle structure of the polycrystalline secondary spherical particles during use, as well as the poor capacity performance of the single crystal during use. By mixing polycrystalline and single crystal materials in a certain proportion, the high capacity of the polycrystalline material is brought into play while taking into account the high compressive strength of the single crystal, thereby improving the oil absorption value of the positive electrode material, making it have the characteristics of high compaction and long cycle.

[0066] In a first aspect, the present application provides a positive electrode material, including a single crystal material and a polycrystalline material, wherein the single crystal material is composed of primary particles, and the polycrystalline material is composed of secondary spherical particles formed by aggregation of primary particles.

[0067] The average particle size D of the positive electrode material satisfies D=D1*K+D2*L, wherein D1 is the average particle size of the single crystal material, D2 is the average particle size of the polycrystalline material, K is the mass percentage of the single crystal material, L is the mass percentage of the polycrystalline material, 3μm<D1<9μm, 10μm<D2<20μm, 0≤K≤1, 0≤L≤1, and K+L=1.

[0068] In a preferred embodiment, 0.6≤K≤1, 0≤L≤0.4, for example, the ratio of K to L may be 0.6:0.4, 0.7:0.3, 0.75:0.25, 0.8:0.2, 0.9:0.1.

[0069] It is understandable that the single crystal material has a small particle size, a large surface atomic ratio, a large specific surface area, and a large surface energy. It is in an energy unstable state and is easy to agglomerate to form secondary particles. It is easy to agglomerate and react with the electrolyte. In addition, the micron-sized single crystal material will cause Li +The diffusion path is longer, resulting in poor reaction kinetics and low capacity. The secondary spherical particles of polycrystalline materials contain multiple primary particles, which makes the reaction kinetics of the structure better and the capacity higher. However, there are a large number of grain boundaries in the structure. During high-temperature cycles and long-cycle charge and discharge processes, due to the insertion and extraction of lithium ions, the lattice constant / unit cell volume changes, generating anisotropic stress, and grain boundary cracking is prone to occur, resulting in particle breakage, affecting the thermal stability of the positive electrode material, and thus related to the storage and safety performance of the battery cell.

[0070] However, compared with polycrystalline secondary spherical particles, single crystal particles have fewer grain boundaries, have better mechanical strength and pressure resistance, and are not easy to break during electrode rolling and charging and discharging. Therefore, mixing single crystal materials and polycrystalline materials as positive electrode materials can not only give full play to the high capacity of polycrystalline materials, but also take into account the high compressive strength performance of single crystal materials, which reduces the gas production of positive electrode materials and improves safety performance.

[0071] Furthermore, after mixing single crystal small particles and polycrystalline large particles in different proportions, the agglomeration of single crystal small particles can be broken up during the mixing process. At the same time, the different surface properties of single crystals and polycrystalline particles are utilized to enable single crystal small particles to be evenly attached around polycrystalline large particles and fill in the gaps between large particles, thereby improving the problem of easy agglomeration of single crystal particles themselves, and enabling the mixed positive electrode material to be stacked more densely, with increased stacking density, thereby improving its electrochemical performance.

[0072] In a second aspect, the present application provides a positive electrode material, including a single crystal material and a polycrystalline material, wherein the single crystal material is composed of primary particles, and the polycrystalline material is composed of secondary spherical particles formed by aggregation of primary particles.

[0073] The positive electrode material satisfies 0.5<N1 / (N1+N2)<1, wherein N1 is the number of primary particles in the cross section of the secondary spherical particles in the cross section of the positive electrode material particles, and N2 is the number of primary particles in the cross section of the positive electrode material particles; and the cross section of the positive electrode material particles contains at least one complete secondary spherical particle.

[0074] In a preferred embodiment, the positive electrode material satisfies 0.8<N1 / (N1+N2)<1.

[0075] It can be understood that the cross-section of the particles of the positive electrode material can more clearly distinguish the mix of single crystal particles and polycrystalline particles therein. At the same time, by calculating the number of primary interfaces in the polycrystalline secondary spherical particles and the number of single crystal primary particles in the cross-section, it can be further verified that the single crystal particles are evenly dispersed around the polycrystalline particles and can fill the gaps between the polycrystalline secondary spherical particles, thereby improving compaction, reducing gas production, and improving cycle performance.

[0076] In combination with the first aspect and / or the second aspect, in a preferred embodiment, the chemical formula of the positive electrode material is: Li a Ni x Co y N z M 1-x-y-z O2, wherein 0.990≤a<1.1, 0.60≤x<1, 0<y<0.3, 0<z<0.3, N is Mn or Al, and M is at least one of Al, Ti, Zr, Mg, Sr, W, Ca, Ba, Nb, W, B, and Y.

[0077] In a preferred embodiment, the surface of the single crystal material and the surface of the polycrystalline material both contain a coating layer.

[0078] It is understandable that surface coating of single crystal materials can reduce the reactive interface between single crystal materials and electrolyte, reduce agglomeration between particles, reduce the surface energy of particles, reduce side reactions, inhibit the dissolution of metal ions, and optimize the material's cycle performance. Surface coating of polycrystalline materials can increase the surface energy of large polycrystalline particles, while reducing surface structural damage caused by friction and collision between large particles, stabilizing oxygen atoms on the material surface, inhibiting changes in the material's surface structure during charging and discharging, and improving its cycle and storage performance.

[0079] In a preferred embodiment, the BET specific surface area of ​​the positive electrode material is 0.1 m 2 / g-1.0m 2 / g, for example, it can be 0.1m 2 / g, 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g or 0.1m 2 / g-1.0m 2 Any value between / g.

[0080] In a preferred embodiment, the oil absorption V of the positive electrode material is ≤30 ml / 100 g.

[0081] It should be noted that the oil absorption can well reflect the comprehensive characteristics of parameters such as the pores between the positive electrode material powder particles, the surface area and the specific surface area. If the oil absorption is different, the particle size, specific surface area and adsorption performance of the positive electrode material powder particles are different. Not only can surface doping modification and surface coating modification affect the oil absorption value of the powder, but the type and position distribution of the particles are also important means to control the oil absorption value of the powder. Therefore, the oil absorption of the positive electrode material can be controlled by adjusting the product parameters in many aspects.

[0082] In a preferred embodiment, the BET specific surface area of ​​the positive electrode material and the oil absorption V of the positive electrode material satisfy: 25.0≤V / BET≤35.0, for example, it can be 25.0, 25.5, 26.0, 28.5, 30.0, 32.5, 35.0 or any value between 25.0 and 35.0.

[0083] When the ratio of the BET specific surface area to the oil absorption of the positive electrode material is within a certain range, it can significantly inhibit a series of side reactions of the positive electrode material in contact with the electrolyte during the cycle process, thereby improving the cycle performance and storage performance of the positive electrode material, inhibiting the gas production of the positive electrode material, and improving its safety performance.

[0084] In a third aspect, the present application also provides a method for preparing the above-mentioned positive electrode material, comprising:

[0085] Polycrystalline positive electrode material and single crystal positive electrode material are prepared respectively using raw materials including positive electrode precursor, lithium source, dopant and coating agent; the polycrystalline positive electrode material and single crystal positive electrode material are mixed in proportion to obtain the positive electrode material.

[0086] In a preferred embodiment, the method for preparing a polycrystalline positive electrode material comprises:

[0087] S1, mixing a positive electrode precursor, a lithium source, and a dopant, and performing a first sintering to obtain a polycrystalline matrix material;

[0088] S2, mixing the polycrystalline matrix material with the coating agent, placing the mixture in a single cone for heat treatment and coating, to obtain a polycrystalline matrix containing a primary coating;

[0089] S3, mixing the polycrystalline substrate containing the primary coating with a coating agent, and performing a second sintering to obtain the polycrystalline positive electrode material.

[0090] More preferably, the molar ratio of the metal element of the positive electrode precursor in S1 to the lithium element in the lithium source is 1:(0.99-1.1), for example, it can be 1:0.99, 1:1, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.1 or any value between 1:(0.99-1.1).

[0091] More preferably, the first sintering of S1 and the second sintering of S3 are both performed under an oxygen atmosphere;

[0092] More preferably, the gas pressure of the first sintering and the second sintering is 5Pa-50Pa, for example, it can be 5Pa, 10Pa, 15Pa, 20Pa, 25Pa, 30Pa, 35Pa, 40Pa, 45Pa, 50Pa or any value between 5Pa-50Pa.

[0093] More preferably, the heating rate of the first sintering in S1 is 1°C / min-5°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between 1°C / min-5°C / min, the temperature is raised to 600°C-800°C, for example, it can be 600°C, 650°C, 700°C, 750°C, 800°C or any value between 600°C-800°C, and the temperature is kept for 5h-10h, for example, it can be 5h, 6h, 7h, 8h, 9h, 10h or any value between 5h-10h.

[0094] More preferably, when S2 is heat-treated and coated, the single cone is in a vacuum state; the temperature of the heat-treatment coating is 150°C-300°C, for example, it can be 150°C, 180°C, 200°C, 250°C, 300°C or any value between 150°C-300°C, and the time is 5h-15h, for example, it can be 5h, 8h, 10h, 12h, 15h or any value between 5h-15h.

[0095] More preferably, the heating rate of the second sintering in S3 is 1°C / min-5°C / min, and the temperature is raised to 250°C-550°C, for example, it can be 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or any value between 250°C-550°C, and kept for 4h-10h, for example, it can be 4h, 6h, 8h, 10h or any value between 4h-10h.

[0096] In a preferred embodiment, a method for preparing a single crystal positive electrode material comprises:

[0097] S001, mixing a positive electrode precursor, a lithium source and a dopant, and performing a third sintering to obtain a single crystal matrix material;

[0098] S002, mixing the single crystal substrate material with the coating agent, and performing a fourth sintering to obtain a single crystal substrate containing a primary coating;

[0099] S003, mixing the single crystal substrate containing the primary coating with a coating agent, and performing a fifth sintering to obtain the single crystal positive electrode material;

[0100] More preferably, the molar ratio of the metal element in the positive electrode precursor to the lithium element in the lithium source in S001 is 1:(0.99-1.1), for example, it can be 1:0.99, 1:1, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.1 or any value between 1:(0.99-1.1).

[0101] More preferably, the third sintering, the fourth sintering and the fifth sintering are all carried out under an oxygen atmosphere, and the gas pressure of the third sintering, the fourth sintering and the fifth sintering is 5Pa-50Pa, for example, it can be 5Pa, 10Pa, 15Pa, 20Pa, 25Pa, 30Pa, 35Pa, 40Pa, 45Pa, 50Pa or any value between 5Pa-50Pa.

[0102] More preferably, the heating rate of the third sintering in S001 is 1°C / min-5°C / min, and the temperature is raised to 700°C-950°C, for example, it can be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or any value between 700°C and 950°C, and kept for 5h-10h, for example, it can be 5h, 6h, 7h, 8h, 9h, 10h or any value between 5h-10h.

[0103] The heating rate of the fourth sintering in S002 is 1℃ / min-10℃ / min, for example, it can be 1℃ / min, 3℃ / min, 5℃ / min, 8℃ / min, 10℃ / min or any value between 1℃ / min-10℃ / min, and the temperature is increased to 550℃-700℃, for example, it can be 550℃, 600℃, 650℃, 700℃ or any value between 550℃-700℃, and kept for 5h-10h, for example, it can be 5h, 6h, 7h, 8h, 9h, 10h or any value between 5h-10h.

[0104] The heating rate of the fifth sintering in S003 is 1℃ / min-5℃ / min, and the temperature is raised to 250℃-500℃, for example, it can be 250℃, 300℃, 350℃, 400℃, 450℃, 500℃ or any value between 250℃-500℃, and kept for 4h-10h, for example, it can be 4h, 6h, 8h, 10h or any value between 4h-10h.

[0105] In a preferred embodiment, whether preparing a polycrystalline positive electrode material or a single crystal positive electrode material, the chemical formula of the positive electrode precursor used in the preparation of the raw material is Ni b Co c N 1-b-c(OH)2, wherein 0.60≤b<1, 0<c<0.3, and N is Mn or Al.

[0106] The lithium source in the raw material includes at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium oxalate, lithium sulfate, lithium chloride and lithium nitrate.

[0107] The dopant in the raw material is selected from oxides or hydroxides containing at least one element of Al, Ti, Zr, Mg, Sr, W, Ca, Ba, Nb, B, and Y, such as Al(OH)3, Al2O3, TiO2, ZrO2, Mg(OH)2, Sr(OH)2, WO3, Ca(OH)2, Ba(OH)2, Nb2O5, B2O3, or Y2O3.

[0108] The coating agent in the raw material includes metal oxides, metal hydroxides, phosphates, sulfates, solid electrolyte materials or conductive polymers.

[0109] In a preferred embodiment, in the positive electrode material, the mass ratio of polycrystalline positive electrode material to single crystal positive electrode material is (10-90):(90-10), for example, it can be 10:90, 20:80, 30:70, 40:60, 50:50, 65:35, 75:25, 85:15 or 90:10.

[0110] In a preferred embodiment, when preparing the positive electrode material, the mixing of the polycrystalline positive electrode material and the single crystal positive electrode material is carried out under the protection of nitrogen gas.

[0111] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0112] Example 1

[0113] This embodiment provides a positive electrode material, including a single crystal positive electrode material and a polycrystalline positive electrode material, and a specific preparation method includes:

[0114] 1. Preparation of polycrystalline positive electrode materials:

[0115] The hydroxide precursor Ni 0.94 Co 0.05 Mn 0.01(OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.05:1, and then dopants ZrO2 and WO3 were added and mixed thoroughly and evenly to obtain a first mixture. The first mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, and the temperature was increased to 700℃ at a heating rate of 2℃ / min, kept at this temperature for 9 hours, and cooled naturally to obtain Li a Ni 0.94 Co 0.05 Mn 0.01 O2 active material matrix;

[0116] The active material matrix and the coating agents Al2O3 and TiO2 are fully and evenly mixed to obtain a second mixture, and the second mixture is placed in a single cone in a vacuum state and stirred and heated to 200° C., kept warm for 5 hours, and cooled naturally to obtain an active material containing the first coating;

[0117] The active material including the first coating is fully and evenly mixed with the coating agent NH4H2PO4 to obtain a third mixture, and the third mixture is placed in a pure oxygen atmosphere. The furnace pressure is controlled at 10Pa, and the temperature is increased to 350°C at a heating rate of 2°C / min. The mixture is kept warm for 10 hours and cooled naturally to obtain a polycrystalline positive electrode material.

[0118] 2. Preparation of single crystal positive electrode materials:

[0119] The hydroxide precursor Ni 0.94 Co 0.05 Mn 0.01 (OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.05:1, and then dopants Sr(OH)2·8H2O, Nb2O5 and Y2O3 were added and mixed thoroughly to obtain a first mixture. The first mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, and the temperature was increased to 750℃ at a heating rate of 2℃ / min, kept at this temperature for 9 hours, and naturally cooled and crushed to obtain Li a Ni 0.94 Co 0.05 Mn 0.01 O2 single crystal matrix material;

[0120] The single crystal substrate material and the coating agents Al2O3 and TiO2 are fully and uniformly mixed to obtain a second mixture, and the second mixture is placed in a pure oxygen atmosphere, the furnace pressure is controlled at 10Pa, the temperature is increased to 680°C at a heating rate of 2°C / min, the temperature is kept for 6 hours, and the temperature is naturally reduced to obtain a single crystal material containing the first coating;

[0121] The single crystal material containing the first coating is fully and evenly mixed with the coating agent NH4H2PO4 to obtain a third mixture, and the third mixture is placed in a pure oxygen atmosphere. The furnace pressure is controlled at 10Pa, and the temperature is increased to 400°C at a heating rate of 2°C / min. The mixture is kept warm for 7 hours and cooled naturally to obtain a single crystal positive electrode material.

[0122] 3. Preparation of positive electrode material: The polycrystalline positive electrode material prepared in 1 and the single crystal positive electrode material prepared in 2 are mixed in a mass ratio of 75:25, and uniformly mixed in a high-speed mixer with nitrogen or PSA protective gas to obtain a blended positive electrode material.

[0123] Example 2

[0124] The same as Example 1, except that the positive electrode material is mixed according to the mass ratio of polycrystalline positive electrode material to single crystal positive electrode material of 80:20.

[0125] Example 3

[0126] The same as Example 1, except that the positive electrode material is mixed according to the mass ratio of polycrystalline positive electrode material to single crystal positive electrode material of 90:10.

[0127] Example 4

[0128] The same as Example 1, except that the positive electrode material is mixed according to the mass ratio of polycrystalline positive electrode material to single crystal positive electrode material of 70:30.

[0129] Example 5

[0130] The same as Example 1, except that the positive electrode material is mixed according to the mass ratio of polycrystalline positive electrode material to single crystal positive electrode material of 60:40.

[0131] Example 6

[0132] The same as Example 1, except that the positive electrode material is mixed according to the mass ratio of polycrystalline positive electrode material to single crystal positive electrode material of 10:90.

[0133] Comparative Example 1

[0134] The positive electrode material provided in this comparative example is only a polycrystalline positive electrode material, and the preparation method of the polycrystalline positive electrode material is the same as that of Example 1.

[0135] Comparative Example 2

[0136] The positive electrode material provided in this comparative example only includes single crystal positive electrode material, and the preparation method of the single crystal positive electrode material is the same as that in Example 1.

[0137] The performance of the positive electrode materials prepared in the above Examples 1-6 and Comparative Examples 1-2 was tested, and the specific testing method is as follows:

[0138] The oil absorption value is tested by using Japan ASAHI SOUKEN S-500. A certain amount of cathode material powder is placed in the mixing chamber, and then linseed oil is dripped on the sample at a constant speed and stirred simultaneously with two motors driving the rotating wings. As the sample absorbs more linseed oil, the mixed material changes from a free-flowing state to a semi-plastic agglomerate. During this process, the viscosity of the mixture gradually increases and a peak value appears. The measurement endpoint is the amount of linseed oil dripped when the torque generated by the change in viscosity characteristics reaches the set value or reaches a constant percentage of the maximum torque obtained from the torque curve, and the oil absorption value (ml / 100g) of the sample to linseed oil is calculated.

[0139] The surface morphology of the samples was observed using a Hitachi S4800 scanning electron microscope.

[0140] The specific surface area of ​​the positive electrode material was tested using the McAb 3020 nitrogen adsorption method.

[0141] The particle size distribution of the positive electrode material particles was obtained by testing the light intensity distribution of laser diffraction using a British Malvern Mastersizer 3000 laser particle size analyzer.

[0142] Test the electrochemical cycle performance: After the prepared positive electrode material is mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 96:2:2, NMP (N-methylpyrrolidone) is added to form a uniform slurry and coated on the copper foil, dried in an oven, and rolled at a pressure of 10Mpa, and cut into a circular pole piece with a diameter of 14mm. The lithium-ion battery is assembled according to the CR2025 button battery in industry, the diaphragm is Cellgard diaphragm, the electrolyte is a 1mol / L LiPF6 solution with EC / PC / DEC as solvent, and the negative electrode is a lithium sheet. The entire assembly process is assembled in a glove box filled with argon, and the oxygen content and moisture content in the glove box are controlled below 0.5ppm. The test conditions of the lithium-ion battery are: the temperature is 25℃±1℃, 45℃±1℃, the voltage range of the charge and discharge cycle is 3.0V-4.3V, the current size is 0.1C, and the cycle test is 0.5C charging and 1C discharging for 50 weeks.

[0143] Gas generation performance of positive electrode material: The positive electrode material prepared above was mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 96:1.5:1.5, and N-methylpyrrolidone (NMP) was added. The mixture was stirred evenly in a vacuum mixer to obtain positive electrode slurry with a designed surface density of 300 g / m 2 -400g / m 2, the positive electrode slurry is evenly coated on aluminum foil (thickness of 16μm), and the coated electrode is dried in an oven at 100℃-130℃, cold pressed, and cut to obtain the positive electrode. The negative electrode active material graphite, binder (sodium carboxymethyl cellulose + styrene butadiene rubber), and conductive agent acetylene black are evenly mixed in a mass ratio of 96:3:1, deionized water is added, and a vacuum mixer is used to prepare the negative electrode slurry, with a designed surface density of 200g / m 2 -300g / m 2 , the mixed slurry is evenly coated on the copper foil (thickness of 8μm), the copper foil is dried at room temperature and then transferred to a 120℃ oven for drying for 1h, the reverse side of the pole piece is treated with the same process, and then the negative pole piece is obtained by cold pressing and slitting. The electrolyte model is TC-E8630J, and the diaphragm is a polypropylene isolation film with a thickness of 16μm. The slit pole pieces are stacked in the order of negative electrode, diaphragm, and positive electrode to make a laminated battery cell, the stacked battery cell is welded through the pole ears, and the welded battery cell is placed in the aluminum-plastic film after punching the pit for packaging, and the electrolyte is injected into the packaged battery cell and sealed to obtain a finished small soft pack battery. After the battery is fully charged to 4.2V at 1C, it is left to stand in a constant temperature box at 80℃ for 3 / 6 / 9 days. The initial volume of the battery and the volume after standing for 3 / 6 / 9 days are determined by the drainage method to obtain the gas production of the battery.

[0144] Figure 1 The low-magnification SEM image of the positive electrode material prepared in Example 1 is shown. Then, the positive electrode material particles prepared in Example 1 are cut open using an argon ion beam cutter, and the particle cross-section is observed by a scanning electron microscope. Figure 2 As shown. Figure 1 and Figure 2 It can be clearly seen that the positive electrode material contains small single crystal particles and large polycrystalline particles, especially Figure 2 The small single crystal particles are evenly dispersed around the large polycrystalline particles and fill the gaps between the large polycrystalline particles.

[0145] Table 1 and Table 2 show the properties of the positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-2.

[0146] Table 1 Test performance of positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-2

[0147]

[0148] Table 2 Gas production of positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-2

[0149]

[0150]

[0151] Figure 3The gas production of the positive electrode materials prepared in the above-mentioned embodiments and comparative examples as the storage time changes are given. It can be clearly seen from the figure that the gas production of the pure polycrystalline positive electrode material prepared in comparative example 1 is the highest, while the gas production of the single crystal and polycrystalline mixed positive electrode materials prepared in the embodiments of the present application is lower than that of comparative example 1.

[0152] Figure 4 The particle size distribution diagram of the positive electrode material prepared in Example 1 is shown, and it can be clearly seen from the figure that the particle size distribution of the positive electrode material has two peaks.

[0153] According to Table 1 and Table 2, when comparing Example 1 and Example 6 with Comparative Example 1 and Comparative Example 2, relative to the ternary positive electrode material products of pure polycrystalline and pure single crystal, the oil absorption V and BET of the positive electrode material products mixed with polycrystalline and single crystal satisfy 25.0≤V / BET≤35.0, and the particle numbers N1 and N2 satisfy 0.8<N1 / (N1+N2)<1. The prepared secondary lithium-ion battery has both high capacity, long cycle and excellent high temperature storage performance, and the performance of the positive electrode material is more balanced, with excellent commercial application prospects.

[0154] In summary, the characteristics of the positive electrode material prepared by the preparation method of the present application are: by mixing polycrystalline and single crystal particles in a certain proportion, the capacity of the polycrystalline material is exerted while taking into account the high compressive strength of the single crystal, and post-processing is performed on the different surface characteristics of the single crystal and the polycrystalline, so that the small single crystal particles can be evenly attached to the large particles and fill the gaps between the large particles, while improving the agglomeration problem of the single crystal particles, so that the mixed positive electrode material can be stacked more densely, the stacking density is increased, the oil absorption value of the positive electrode material is improved, and the V oil absorption value and the V / BET value of the BET specific surface area are controlled within a certain range. It can significantly inhibit a series of side reactions of the positive electrode material in contact with the electrolyte during the cycle, so as to improve the cycle performance and storage performance of the material, inhibit the gas production of the material, and improve its safety performance.

[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0156] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, any of the above-mentioned claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A positive electrode material, characterized in that: It includes single crystal material and polycrystalline material, wherein the single crystal material is composed of primary particles, and the polycrystalline material is composed of secondary spherical particles formed by aggregation of primary particles; The particle size distribution of the positive electrode material is a bimodal distribution, and the average particle size D of the positive electrode material satisfies D=D1*K+D2*L, wherein D1 is the average particle size of the single crystal material corresponding to the first peak in the bimodal distribution, D2 is the average particle size of the polycrystalline material corresponding to the second peak in the bimodal distribution, K is the mass percentage of the single crystal material, L is the mass percentage of the polycrystalline material, 3μm<D1<9μm, 10μm<D2<20μm, 0≤K≤1, 0≤L≤1, and K+L=1.

2. A positive electrode material, characterized in that: It includes single crystal material and polycrystalline material, wherein the single crystal material is composed of primary particles, and the polycrystalline material is composed of secondary spherical particles formed by aggregation of primary particles; The positive electrode material satisfies 0.4<N1 / (N1+N2)<1, wherein N1 is the number of primary particles in the cross-section of the secondary spherical particles in the cross-section of the positive electrode material particles, N2 is the number of primary particles in the cross-section of the positive electrode material particles, and the cross-section of the positive electrode material particles contains at least one complete secondary spherical particle.

3. The positive electrode material according to claim 2, characterized in that The positive electrode material satisfies 0.8<N1 / (N1+N2)<1.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that At least one of the following conditions is met: A. The general chemical formula of the positive electrode material is: Li a Ni x Co y N z M 1-x-y-z O2, wherein 0.990≤a<1.1, 0.60≤x<1, 0<y<0.3, 0<z<0.3, N is Mn or Al, and M is at least one of Al, Ti, Zr, Mg, Sr, W, Ca, Ba, Nb, W, B, and Y; B. The surface of the single crystal material and the surface of the polycrystalline material both contain a coating layer; C. The BET specific surface area of ​​the positive electrode material is 0.1 m 2 / g-1.0m 2 / g; D. The oil absorption of the positive electrode material V≤30ml / 100g; E. The BET specific surface area of ​​the positive electrode material and the oil absorption V of the positive electrode material satisfy: 25.0≤V / BET≤35.

0.

5. A method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: include: Using raw materials including a positive electrode precursor, a lithium source, a dopant and a coating agent, polycrystalline positive electrode materials and single crystal positive electrode materials are prepared respectively; The polycrystalline positive electrode material and the single crystal positive electrode material are mixed in proportion to obtain the positive electrode material.

6. The preparation method according to claim 5, characterized in that: At least one of the following conditions is met: (1) The preparation method of the polycrystalline positive electrode material comprises: mixing the positive electrode precursor, the lithium source and the dopant, and performing a first sintering to obtain a polycrystalline matrix material; mixing the polycrystalline matrix material with the coating agent, placing the polycrystalline matrix material in a single cone for heat treatment and coating, and obtaining a polycrystalline matrix containing a primary coating; mixing the polycrystalline matrix containing the primary coating with the coating agent, and performing a second sintering to obtain the polycrystalline positive electrode material; (2) The method for preparing the single crystal positive electrode material comprises: mixing the positive electrode precursor, the lithium source and the dopant, and performing a third sintering to obtain a single crystal matrix material; mixing the single crystal matrix material with the coating agent, and performing a fourth sintering to obtain a single crystal matrix containing a primary coating; mixing the single crystal matrix containing a primary coating with the coating agent, and performing a fifth sintering to obtain the single crystal positive electrode material.

7. The preparation method according to claim 6, characterized in that: The method for preparing the polycrystalline positive electrode material satisfies at least one of the following conditions: (3) The molar ratio of the metal element in the positive electrode precursor to the lithium element in the lithium source is 1: (0.99-1.1); (4) The first sintering and the second sintering are both carried out in an oxygen atmosphere; (5) The gas pressure of the first sintering and the second sintering is 5Pa-20Pa; (6) The first sintering heating rate is 1 ° C / min-5 ° C / min, the temperature is raised to 600 ° C -800 ° C, and the temperature is kept for 5h-10h; (7) When the heat treatment coating is performed, the single cone is in a vacuum state; (8) The heat treatment coating temperature is 150 ℃ -300 ℃, the time is 5h-15h; (9) The heating rate of the second sintering is 1℃ / min-5℃ / min, the temperature is raised to 250℃-550℃, and the temperature is kept for 4h-10h.

8. The preparation method according to claim 6, characterized in that: The method for preparing the single crystal positive electrode material satisfies at least one of the following conditions: (10) The molar ratio of the metal element in the positive electrode precursor to the lithium element in the lithium source is 1: (0.99-1.1); (11) The third sintering, the fourth sintering and the fifth sintering are all carried out in an oxygen atmosphere; (12) The gas pressure of the third sintering, the fourth sintering and the fifth sintering is 5Pa-20Pa; (13) The heating rate of the third sintering is 1°C / min-5°C / min, the temperature is raised to 700°C-950°C, and the temperature is kept for 5h-10h; (14) The heating rate of the fourth sintering is 1 ° C / min-5 ° C / min, the temperature is raised to 550 ° C -700 ° C, and the temperature is kept for 5h-10h; (15) The heating rate of the fifth sintering is 1°C / min-5°C / min, the temperature is raised to 250°C-500°C, and the temperature is kept for 4h-10h.

9. The preparation method according to any one of claims 5 to 8, characterized in that: At least one of the following conditions is met: (16) The chemical formula of the positive electrode precursor is Ni b Co c N 1-b-c (OH)2, wherein 0.60≤b<1, 0<c<0.3, and N is Mn or Al; (17) The lithium source comprises at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium oxalate, lithium sulfate, lithium chloride and lithium nitrate; (18) The dopant is selected from an oxide or hydroxide containing at least one element of Al, Ti, Zr, Mg, Sr, W, Ca, Ba, Nb, B, and Y; (19) The coating agent includes a metal oxide, a metal hydroxide, a phosphate, a sulfate, a solid electrolyte material or a conductive polymer; (20) The mass ratio of the polycrystalline positive electrode material to the single crystal positive electrode material is (10-90): (90-10); (21) The mixing of the polycrystalline positive electrode material and the single crystal positive electrode material is carried out under the protection of nitrogen gas.

10. A lithium ion battery, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 4.

Citation Information

Cited By

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN120527379A

  • Cathode material, preparation method thereof and lithium ion battery

    CN120527379B